KARAKTERISTIK BRIKET DARI KOMPOSIT SAMPAH BUAH, SAMPAH PLASTIK HIGH DENSITY POLYETHYLENE (HDPE) DAN TEMPURUNG KELAPA SEBAGAI BAHAN BAKAR ALTERNATIF DI RUMAH TANGGA - Ruslinda, Yenni; Husna, Fitratul; Nabila, Arum (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2017)
This study aims to examine the characteristics of briquettes from fruit waste, HDPE plastic waste, and coconut shell composite, as an alternative fuel. Characteristic tests include physical characteristics (density and compressive strength), chemical characteristics (moisture, volatile content, fixed carbon, ash content, calorific value), and cost calculation for making briquettes. Physical characteristics tests obtained that density is between 0.60 to 0.89 g/cm3 and compressive strength is between 0.88 to 6.87 kg/cm2. Chemical characteristics tests found that water content 5.73 - 9.06%; volatile content 70.02 - 79.92%; fixed carbon 12.39 - 18.41%; ash content of 1.47 - 4.86%, and calorific value 4549 - 7213 cal/g. Cost for making briquettes range between 0.56 to 0.86 rupiahs/kcal. Except for compressive strength parameter, other parameters are in the standard range of biobriquettes quality according to Permen ESDM No. 047 Tahun 2006. Optimum briquette found in this research is a mixture of 20% fruit waste, 20% of plastic waste HDPE, and 60% coconut shell. Briquettes made as a mixture of those three raw material with that composition is optimum as an alternative fuel, because it produces higher calorific value and lower cost.Â